Lung cavitation as a long-term imaging pattern of covid-19 - KOCAKAYA, DERYA (My University, 2023)
Background A wide variety of radiological imaging findings, especially CT findings, have been reported in patients with COVID-19 pneumonia during the pandemic surge. Generally, on control chest imaging, individuals who have been cured of the disease usually show complete remission; however, in severe cases, residual pulmonary fibrosis, other abnormalities, and, rarely, lung cavitation can be observed. In this retrospective descriptive study, we aimed to describe the clinical, radiological, and laboratory characteristics of patients who developed lung cavitation in the course of SARS-CoV-2 disease recovery. Methodology Over a period of five months from March 1, 2021, to August 1, 2021, 15 consecutive patients who developed cavitary lesions on chest CT during the course of recovery from COVID-19 were recruited as the study population. All patients had a history of a SARS-CoV-2 infection diagnosed with a positive real-time polymerase chain reaction test. Patients who already had cavitary lesions in chest CT during the start of COVID-19 symptoms were excluded. Results In this study, 14 patients were male (93.3%). The only female patient was the only severely obese patient in the study population, with a body mass index was 40.4 kg/m2 . The median (range) age of the patient population was 61 (42-79) years. Eight patients (53.3%) required intensive care unit admission during the hospitalization period. Three patients who required intensive care unit were intubated and needed invasive mechanical ventilation. Two patients died during hospitalization. Conclusions Lung cavitation remains a rare occurrence in the course of COVID-19. Bronchoscopic evaluation and scanning for pulmonary embolism should be done in appropriate patients to determine secondary reasons for cavitation. Although this descriptive study showed that cavitary lesions can develop in patients with severe disease, more comprehensive studies with a control group are needed to reach a definitive conclusion.
Keywords: long covid-19; post-covid-19; computerized tomography; lung cavitation; covid-19